السيرة الذاتية للكاتب الطيب صالح والكاتب تشيان جون شوو: دراسة مقارنة - الهلف، أحمد عبدالرحمن عباس Alhelf, Ahmed Abdulrahman Abbas (جامعة قناة السويس - كلية الآداب والعلوم الإنسانية, 2022)
تنفرد كل من الصين والسودان بتاريخ حضاري وثقافي بارز، يمتد لآلاف السنين، فقد تشابهت الظروف التاريخية والحضارية بين الشعبين العريقين، فقد قامت الحضارة السودانية على ضفاف نهر النيل العظيم، وكذلك الحضارة الصينية القديمة قامت على ضفاف نهر اليانغستي، فقد كانت لغتهم ونقوشهم خير دليل على ذلك. من هنا كان التشابه بين الحضارتين في كثير من المواطن، فلا عجب أن تشابهت بعض الأعمال الأدبية والفكرية والثقافية، ولذا نجد أن الحضارتين السودانية العربية والصينية يطلق عليهما "الحضارة الشرقية"، لما تتمتع به الحضارتين من أفكار ثقافية وتاريخ مشترك، بدأ منذ ظهور طريق التجارة المعروف باسم "طريق الحرير". يعد التشابه التاريخي والحضاري والثقافي والفكري هو الدافع والمحرك الرئيس للبحث في أعمال أدبية وفكرية مشتركة، ولذا قامت الدراسة على البحث عن التشابه والاختلاف بين عملاقين الأدب العربي والصيني، وهما الكاتب تشيان جو شوو والكاتب الطيب صالح. يتناول هذا البحث دراسة السيرة الذاتية للكاتب تشيان جون شوو والكاتب الطيب صالح، وأهم وأبرز أعمالهم الأدبية، كما نسلط الضوء على الظروف التاريخية والاجتماعية والبيئية التي نشأ فيها كلا الكاتبين، ومن خلال هذا العرض البسيط نستطيع فهم الأسباب التي دفعت كلا الكاتبين إلى كتابة أعمالهم الأدبية، ونعرف أسباب النجاح الباهر الذي حققته أعمالهم الأدبية. يعرض لنا هذا البحث أهم الجوانب الاجتماعية والفكرية للكاتب تشيان جون شوو والكاتب الطيب صالح، ومن خلال هذا العرض نستطيع فهم الأسباب التي دفعتهما إلى الكتابة، وعقد مقارنة بسيطة بين الكاتبين ومعرفة أوجه التشابه والاختلاف بينهما، وموقف كلاهما من الحضارة الشرقية والغربية، والأسباب التي دفعت الكاتب لكتابة أعماله الأدبية المرموقة والبارزة، ونجاح هذه الأعمال الأدبية. Both China and Sudan have a distinguished civilization and cultural history that extends for thousands of years, as the historical and civilization conditions are similar between the two ancient peoples, as the Sudanese civilization was established on the banks of the great Nile River, as well as the ancient Chinese civilization that was established on the banks of the Yangtze River, as their language and inscriptions were the best evidence On it. Hence the similarity between the two civilizations in many citizens, so it is not surprising that we find many similarities in some literary', intellectual and cultural works. Therefore, we find that the Sudanese and Chinese civilizations are called "the Eastern civilization", because of the cultural ideas and common history of the two civilizations, which began since the trade road known as the "Silk Road". The historical, civilization, cultural and intellectual similarity is the main motivation for research in joint literary and intellectual works. Therefore, the study was based on searching for the similarity and difference between the two greatest Arabic and Chinese literature writers, the writers are Qian Zhong Shu and Tayeb Salih. This research focused on the study of the biography of Qian Zhong Shu and writer Tayeb Salih, and their most important and prominent literary works. We also highlight the historical, social and environmental conditions in which both of writers grew up, and through this simple presentation we can understand the reasons that led both of writers to write their literary works. We will know the success reasons for the their literary works. This research shows us the most important social and intellectual aspects of the writer Qian Zhong Shu and the writer Tayeb Salih, and through this presentation we can understand the reasons that prompted them to write, we also make a simple comparison between the two writers and learn the similarities and differences between them, their views on the eastern and western civilization, and the reasons that prompted the writer to write his famous literary works.
Keywords: السير الذاتية -- شوو، تشيان جون -- الحضارة الصينية -- الأعمال الأدبية -- الأدب الصيني -- أحمد، الطيب محمد صالح، ت. 2009 م